Crianças que se revelam agressivas: um estudo fenomenológico sobre o reconhecimento da agressividade em escolares - RIBEIRO, Elizabete Cristina Monteiro (Universidade Federal do Pará, 2014)
The aggressiveness in childhood has been presented as a recurrent complaint by parents and teachers, which introduces a worrying scenario in that the identification of the child and his family as primary responsibility is still sharp. This study present a childhood aggression initial understanding from the Person-Centered Approach, as like the education proposed in this reference articulating with some complexity theory principles. Considering that the child recognized as aggressive has been made in a subjectivity process which significant socially people are involved, this research through a phenomenological research aimed to check the recognition configuration from the participants testimonies analysis: the child identified as aggressive, a colleague, the mother and teacher. The study was done in a selected school from the mapping by the Centre of Violence in Schools Core-Pa. The results point to: a subjectivity vision subsidizing the linear link form, the distance used as a teaching resource to avoid the conflict, the previous manifested aggression denouncing the student stories and current experience, a relationship between the child condition to react label and family history, the repercussions of how it is recognized at school in their learning process. The participants experienced feelings allow us to pay attention to the condition involvement that includes then, reaffirming the need to seek ways to promote changes in the student and the school seeing way. This changes must be introduced from a complex interactive subjectivity human vision, enabling understand the aggressiveness subjectivity from a scenario that may reveal multiple meanings.